Spatial Disparity on the Impact of Real Estate Investment on Regional Economy in China: MGWR Approach - Zheng, Hua (Colombo Economic Journal, 2024)
This paper explores, for the first time, the regional disparity in the relationship between real estate investment and regional economic performance using quantitative and visual approaches. By introducing the MGWR (Multi-Scaled Geographically Weighted Regression) model, we conduct a regression analysis on cross-sectional urban data for 2020. The findings reveal that the greatest contribution to regional economies is made by economically developed regions along the eastern coast, as well as some inland cities such as Baotou, Hohhot, and Taiyuan, followed by the eastern and southeastern coastal areas and the centralwestern regions. In contrast, real estate investment in the western region contributes the least to regional economic development.
Keywords: Real Estate Investment; China; Regional Disparity; MGWR; Spatial Econometrics